Data manipulation with R : efficiently perform data manipulation using the split-apply-combine strategy in R - Abedin, Jaynal; Das, Kishor Kumar (Packt Publishing, 2015)
This book is for all those who wish to learn about data manipulation from scratch and excel at aggregating data effectively. It is expected that you have basic knowledge of R and have previously done some basic administration work with R.
Includes index.
Keywords: R (Computer program language); Statistics -- Data processing.; Electronic books.; elektronické knihy; electronic books